Respuestas
Respuesta dada por:
33
E = V.T
![120km = V.(3h)
120km = V.(3h)](https://tex.z-dn.net/?f=120km+%3D+V.%283h%29%0A%0A)
![\frac{120km}{3h} = V \frac{120km}{3h} = V](https://tex.z-dn.net/?f=+%5Cfrac%7B120km%7D%7B3h%7D+%3D+V)
![\frac{40km}{h} = V \frac{40km}{h} = V](https://tex.z-dn.net/?f=+%5Cfrac%7B40km%7D%7Bh%7D++%3D+V)
Respuesta dada por:
2
Respuesta:
E = V.T
120km = V.(3h)120km=V.(3h)
\frac{120km}{3h} = V
3h
120km
=V
\frac{40km}{h} = V
h
40km
=V
Notas:
Coronita plis ❤️
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años